Legal Sanctions for Child Rape in Indonesia: A Comparative Study of National Law and Islamic Criminal Law - Nasution, Muhammad Syauqi; Ramadani, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study examines the legal framework surrounding child rape cases in Indonesia by comparing national law and Islamic criminal law. The purpose of this research is to assess the effectiveness of existing legal sanctions and explore the relevance of Islamic principles, particularly hudud and ta’zir, in addressing such crimes. Given the severe psychological and social consequences for victims, an evaluation of whether current penalties provide sufficient deterrence and justice is necessary. This study employs a qualitative legal research methodology, utilizing a normative-juridical approach. Data collection includes an analysis of statutory regulations, court decisions, and Islamic legal principles. The study focuses on Putusan Nomor 1590/Pid.Sus/2023/PN.Mdn as a case study, alongside an examination of the Child Protection Law and Islamic criminal law doctrines. The findings reveal that both national and Islamic law recognize child rape as a grave offense requiring strict punishment. While Indonesian law mandates imprisonment for perpetrators, Islamic law prescribes hudud or ta’zir penalties, depending on the offender’s status. However, questions remain regarding whether national legal sanctions are adequate in providing justice and deterrence. This research offers an original contribution by bridging the gap between national law and Islamic criminal law in the context of child protection. It highlights the potential incorporation of ta’zir-based punishments into Indonesia’s legal framework to enhance judicial flexibility. The study’s implications suggest the need for legal reform to strengthen child protection laws by integrating principles of Islamic criminal law. This could ensure more effective deterrence and greater justice for victims.